Prevalence of Neisseria gonorrhoeae infection among women of reproductive age in sub-Saharan Africa: a systematic review and meta-analysis. (2nd September 2020) - Kassa, Zemenu Yohannes; Hussen, Siraj; Hadra, Nebiha; Moges, Yohannes; Bonja, Fisseha
Abstract: Objective: Neisseria gonorrhoeae infection is a global, major public health problem. It is the second leading bacterial sexually transmitted infection (STI) in sub-Saharan Africa and worldwide. As study findings on the topic are inconsistent, we conducted a systematic review and meta-analysis to determine the pooled prevalence of N. gonorrhoeae infection in sub-Saharan Africa among reproductive-aged women. Methods: Published studies were systematically retrieved from PubMed, Embase, CINHAL and Science Direct. Their quality was measured using the Joanna Briggs Institute critical appraisal checklist for studies reporting prevalence data, and the score of each included study had to meet at least 4.5 out of 9 indicators of quality. Results: The meta-analysis of 35 studies showed that the pooled prevalence of N. gonorrhoeae infection among reproductive-aged women in sub-Saharan Africa was 3.28% (95% confidence interval 2.61%, 3.94%). Conclusion: The prevalence of N. gonorrhoeae infection was higher than that found in other studies carried out in the region. The results suggest that greater attention should be paid to the primary prevention of N. gonorrhoeae. We recommend the implementation of STI education for reproductive-aged women and the use of specific and rapid diagnostic testing for N. gonorrhoeae infection in STI clinics. N. gonorrhoeae screening and treatment should be integrated into in- and outpatient clinics to reduce infection among reproductive-aged women.